Geochemistry and remediation of Fe, Mn, and as in groundwater from quaternary alluvium, lower Kelantan Basin, North-Eastern Coast of Peninsular Malaysia / Usman Abdullahi Usman - Usman Abdullahi , Usman (2021)
The lower Kelantan Basin is predominantly drained by Kelantan, SemeFrak, Kemasin, and Pengkalan Datu rivers. The Kelantan river traverses about 85 percent of Kelantan state. These fluvial systems flow towards the northwest before discharging into the South China Sea. Application of thin-section petrography, field emission scanning electron microscopy and energy dispersive X-ray analysis (FESEM-EDX), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermo-analysis, and laser Raman spectral analysis methods can be combined to characterize iron-ores and distinguish clay minerals in alluvial soils. The integrated methodology developed for this work provides the basis for a generic mineral characterization toolkit. Five main alluvial soil types have been defined in the upper layer of the lower Kelantan Basin, Malaysia: sand with low clay content, clay sand, sandy clay, mottled clay, and mud-sand. The soils contain significant concentrations of iron-ore minerals, kaolinite, chlorite and subordinate illite. The groundwater pH ranges from 5.14 to 8.75 which shows the slightly acidic to alkaline character of the aquifers discharge to gaining streams. The average abundance of cations in solutions is Na+ > Ca+ > K+ > Mg+2, and anions HCO3- > Cl-1 > SO4 -2. Groundwater hydrochemical facies are dominated by Na - HCO3 groundwater types. Coupled models of the upper layer mineral compositions and aqueous geochemistry are used to establish the sources of iron and manganese in the groundwater of lower Kelantan Basin. High concentrations of dissolved iron and manganese in the groundwater of the lower Kelantan Basin are related to sodium chloride groundwater types. Thermodynamic modelling of Fe2+/Fe3+ and S2-/SO4 2- redox pairs shows the state of redox disequilibrium in the groundwater. The redox state controls mineral precipitation and dissolution of iron oxyhydroxides and acid volatile sulphides. The speciation modelling of the groundwater samples show the presence of ferric iron complexes and aqueous sulphides, despite supersaturation with respect to hematite, goethite, and pyrite. Dissolved manganese in the groundwater possibly originated from the dissolution of amorphous oxide-hydroxide and siderite, having substituted for iron as a minor impurity. The research study was carried out to evaluate trace metals concentrations in groundwater of Lorong Serai 4, Hulu Langat, Selangor, Malaysia. The results show that the concentration level Fe, Mn and As concentrations exceed their acceptable limit. The groundwater geochemical data of the area are used in establishing the source of Fe, Mn and As metal ions. Evaluation of Fe2+/Fe3+ and S2-/SO4 2- redox couples and thermodynamic modelling indicates that the groundwater of the area in redox disequilibrium. Aqueous arsenic and manganese are possibly derived from the dissolution of pyrite (arsenopyrite) and amorphous oxidehydroxides, respectively. The high concentration of iron in the shallow groundwater in the area primarily the result of silicate rock weathering of ferroan igneous and metamorphic minerals with a minor contribution from the oxidation of iron sulfides. Magnetite coated with graphene oxide (Fe3O4-GO) nanoparticles (NPs), were synthesized, characterized and the adsorption preliminary experiments were carried out and the Fe3O4-GO NPs show enhanced removal (Fe > As > Mn) capacity over graphene oxide (GO).